Quality of life and its associated factors among women with pelvic organ prolapse who attend gynecology clinics Southern Ethiopia 2022 - Ayenew Tega; Fentahun Yenealem; Getahun Belay; Eden Asmare; Temesgen Getaneh; Misgana Desalegn; Natnael Dechasa; Zemenu Addis (BMC Women's Health, 2024)
Abstract Introduction Pelvic organ prolapse is the implosion of one or more pelvic floor structures which affect womens quality of life by compromising overall health, physical, social, structural, functional and emotional well-being. Objective To assess the quality of life and its associated factors among women with pelvic organ prolapse who attend gynecology clinics at Gurage zone hospitals, Southern Ethiopia 2022. Methods Facility-based cross-sectional study was applied in gurage zone hospital from April, 30 to Jun 30, 2022. Systematic random sampling was employed to select 416 women. Interview based structured questionnaires were applied to collect the data. The collected data were analyzed using Statistical Produte and Service Solution. Binary and multivariable logistic regressions were fitted to assess the association between dependent and independent variables. P-value < 0.05 was used to declare the final statistical significance. Result The mean (SD) score of quality of life in this study was 53.57 (21.59). The most affected domains were general health perception and physical limitation (mean (SD) score 67.45 29.24) and (64.26 32.36)) respectively. Had no formal education (AOR = 1.50, 95% CI: 1.02, 3.12), stage III/IV POP (AOR = 2.02, 95% CI: 1.19, 3.60), constipation (AOR = 3.51, 95% CI: 2.12, 7.21), urge urinary incontinence (AOR = 3.89, 95% CI: 2.32, 6.95), and not did regular physical exercise (AOR = 2.18, 95% CI: 1.41, 3.37) were significantly associated with poor quality of life. Conclusion More than half of the participants in this study had impaired quality of life. The factor associated with quality of life was had no formal education, stage III/IV, constipation, urge urinary incontinence, and regular physical activity. It is recommended to have access education, counseling regular physical activity, detection, and management of its comorbidity.